Keeping good friends close – The surface and secreted proteomes of a probiotic bacterium provide candidate proteins for intestinal attachment and communication with the host. Issue 11 (8th June 2017) - Jeffery, Constance J.
Abstract : Bacteria use cell surface proteins and secreted proteins to interact with host tissues. Several dozen previously published proteomics studies have identified cell surface proteins for pathogens. In this issue, Celebioglu and Svensson (Proteomics 2017, 17, 1700019) use 2D gel electrophoresis and mass spectrometry to identify secreted and cell surface proteins of a commensual gut bacterium, Lactobacillus acidophilus NCFM. Some of the proteins are known to have functions in the cytoplasm, and their presence on the cell surface suggests they might be moonlighting proteins. In addition, comparisons of proteins used by pathogenic and probiotic species to interact with their hosts could lead to improved treatments of infections and chronic diseases that are associated with an imbalance of pathogenic and probiotic gut bacteria.